(untitled) - Felix, S. (Delhi, 2018)
Content: Shrimp culture systems; water quality management; stocking management; shrimp nutrition and feed management; shrimp racewways.
Keywords: Aquaculture,Nuôi trồng thủy sản,Shrimp culture.,Kỹ thuật nuôi tôm